Potential Food Crop Production and Food Security in Kampar regency of Riau Province - Bernard Isyandi (TRIKONOMIKA, 2016)
Objectives of this study is to determine the economic and social benefits in building a regional scale of agricultural economy and influence over the land in relation to the development of food security and economic. This study was conducted through a survey method in Kampar District of Riau Province. The variables measured are determinants of crop production and food security. The results found that the area is faced with a decline in the production of rice and pulses which have an impact on rice shortage which was also caused by the potential not yet optimal management of land resources as a whole. The result showed that agricultural land, the number of seeds, fertilizers, insecticides and labor, both partialy and simultaneously, effect the food security in Kampar District.